Prevalence, Incidence, Influence Factors, and Cognitive Characteristics of Amnestic Mild Cognitive Impairment Among Older Adult: A 1-Year Follow-Up Study in China - Li, Wei; Sun, Lin; Xiao, Shifu (Frontiers in Psychiatry, 2020)
Abstract. Background: The risk and protective factors of amnestic Mild Cognitive Impairment (aMCI) and its prevalence as well as incidence among the elderly in Chinese community are still unclear. Methods: We carried out this 1-year longitudinal study to survey a random sample of 3246 community elders aged 60 and over in China. All subjects were required to complete a comprehensive clinical assessment, physical examination and several neuropsychological tests at baseline and follow-up. What’s more, we also collected their lifestyle information by a standardized questionnaire. Results: We found that the prevalence of aMCI was 17.1%, while the incidence of aMCI among Chinese elderly was 70.57 per 1,000 person-years. By using Cox regression analysis, we found that men (p=0.001, OR=0.489, 95%CI 0.319~0.751) and reading (p=0.023, OR=0.533, 95%CI 0.310~0.917) were protective factors for against aMCI. The elderly who developed aMCI in the future showed multiple cognitive impairments (such as immediate memory, associative learning memory and excutive function) in their early stage, and Wechsler’s Block Design (p=0.027, OR=0.969, 95%CL 0.943~0.996) could predict whether subjects would turn into aMCI in the fucture. Conclusions The present study suggests that aMCI is a considerable health problem in China. Executive dysfunction may be an indicator of the future development of aMCI in the normal elderly.